Meal timing relative to DLMO: Associations with BMI and Body Fat - Culnan, Elizabeth (Sleep Health, 2021)
BACKGROUND: Timing of eating relative to the dim light melatonin onset (DLMO) may serve as a modifiable risk factor for adverse cardiometabolic outcomes. The primary aim of this study was to examine whether the timing of eating relative to DLMO is associated with BMI, body fat, and diet in healthy adults without the confound of sleep deprivation. METHODS: Healthy men and women (N = 97), ages 18–50, with a habitual sleep duration of ≥ 6.5 hours and ≤ 8.5 hours completed 7 days of actigraphy and daily sleep and food diaries. Participants underwent a DXA scan and blood draws to assess DLMO in the clinical research unit. RESULTS: A shorter duration between DLMO and the average clock time of the last meal (last meal-DLMO) was related to a higher number of meals consumed, b = .25, SE(b) = .06, p < .001, longer feeding duration, b = .84, SE(b) = .06, p < .001, greater carbohydrate intake, b = 9.08, SE(b) = 3.55, p = .01, and greater sugar intake, b = 4.73, SE(b) = 1.83, p = .01. Last meal-DLMO was not associated with BMI in the full sample; however, among those with later DLMO (after 10:30pm) last meal-DLMO was related to higher BMI, b = .92, SE(b) =.36, p = .02. CONCLUSION: These results suggest that timing of last meal relative to DLMO may serve as a marker of circadian misalignment and that eating the last meal closer to DLMO may negatively impact dietary habits.